Quantitative evaluation of impact attenuation by football helmets using a modal impulse hammer. (June 2019) - Cummiskey, Brian; Sankaran, Goutham N; McIver, Kevin G; Shyu, Daniel; Markel, Justin; Talavage, Thomas M; Leverenz, Larry; Meyer, Janette J; Adams, Douglas; Nauman, Eric A
Concussions and changes in neurophysiology due to sub-concussive blows are common in contact sports, motivating a need for improved safety systems. While there have been attempts to determine whether or not new helmet designs influence the incidence of concussion, the results to date have been inconclusive. Consequently, the goal of this study was to evaluate the ability of modern football helmets to mitigate linear impacts directed normal, as well as oblique, to the surface of the helmeted head using a system that quantifies both the input load and the resulting accelerations of a Hybrid III headform. The transfer function connecting the inputs and outputs of the system was developed using dimensional analysis to provide a means of comparing helmets across brands and sports. For translational accelerations, increased helmet mass and a secondary layer of padding helped mitigate the impacts. The attenuation of angular accelerations depended substantially on helmet model and impact location.